15a Conferenza Italiana degli Utenti Esri: l'intelligenza del territorio per tracciare il futuro - Fulvio Bernardini (GEOmedia, 2014)
For fifteen years now the Italian community of GIS come across in the context of Esri User Conference. Held in Rome at the Auditorium del Massimo on 9 and 10 April, the conference was an opportunity to take stock of the situation in the field of Geographic Information Systems. More than 1500 people from all over Italy and other European countries were present in Rome; 150 works were submitted, 10technology workshops, 7 training courses-videos, 14 sessions aimed at users. The organization has been able to renew the offer of the conference, proposing important changes in the program and a dynamic management of the plenary session, an important stage useful to perceive the dynamics of change that currently cross the GIS industry.